Pengaruh Employee Engagement, Beban Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Moderasi - Kurniawan, Brahma Wahyu; Kusumawardani, Mawar Ratih (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2024)
This research purpose is to examine the influence of employee engagement, workload on employee performance with job satisfaction as a moderating variable. The population used in this research were all employees at the KKDR City Regional Secretariat Office. Sampling used a non probability sampling technique with a purposive sampling method, totaling 112 respondents all civil servants at the KKDR City Regional Secretariat Office. The variables used in this research are employee engagement, workload, job satisfaction and employee performance measured with 1-5 likert scale. This research uses path analysis using SPSS. The results of this research show: 1) Employee engagement influences job satisfaction so that the first hypothesis (H1) is accepted, 2) Employee engagement influences employee performance so the second hypothesis (H2) is accepted, 3) Workload influences job satisfaction so the third hypothesis (H3) is accepted, 4) Workload influences employee performance so the fourth hypothesis (H4) is accepted, 5) Job satisfaction influences employee performance so that the sixth hypothesis (H6) is accepted, 6) Employee engagement influences employee performance with job satisfaction as a moderating variable so that the sixth hypothesis (H6) is accepted, 7) Workload influences employee performance with job satisfaction as a moderating variable so the seventh hypothesis (H7) is accepted.